Utilization of Water Spinach Harvest Waste as Liquid Organic Fertilizer and Compost on the Growth and Yield of Large Chili Plants (Capsicum Annuum L.) - Nurlailah Mappanganro; Baiq Inggar Linggarweni; Nirmawati Nirmawati (Postgraduate, University of Mataram, 2023)
The aim of the research was to determine the effect of giving concentrations of liquid organic fertilizer and doses of compost from water spinach harvest waste on the growth and yield of large chili plants (Capsicum annuum L.). The results of the research showed that the administration of various concentrations of LOF and doses of compost from kale harvest waste had a significant effect on the height of large chili plants (Capsicum annuum L.) at 84 DAP, and had no significant effect on the number of leaves at 84 DAP, flowering age, number of flowers and the number of large chili plants (Capsicum annuum L.). The combination of 5 ml/l LOF and no compost (P1K0) treatment resulted in the highest average plant height at 84 DAP (38.33 cm), and the highest average number of plant leaves (56.00). The combination of treatment with a LOF concentration of 5 ml/l and the addition of 250 g compost per plant (P1K1) resulted in the fastest average flowering age (18.67 DAP). The combination of treatment with a LOF concentration of 10 ml/l and the addition of 250 g compost per plant (P2K1) produced the highest average number of flowers (10.33 pieces) and also produced the highest average number of fruit (2.33 pieces).